Polydimethylsiloxane as protecting layer to improve the quality of patterns on graphene oxide. (October 2022) - Cutroneo, Mariapompea; Havranek, Vladimir; Torrisi, Lorenzo; Mackova, Anna; Malinsky, Petr; Fazio, Barbara; Slepicka, Petr; Fajstavr, Dominik; Silipigni, Letteria
Abstract: Graphene oxide (GO) foils have been covered with poly(dimethylsiloxane) (PDMS) via spin coating and then heated in oven to strengthen the bond of the polymerized composite. Micro ion beam has been used to directly pattern the realized film and to promote the localized reduction in the ion irradiated GO areas in vacuum. The lessening of the disorder in the carbon crystal structure and the defects production are demanding in all the graphene-based materials applications. Micro beams of 5 MeV C 3+ ions with a spot of 1.5 μm × 10 μm (focused beam) and unfocused beams with size of 3 × 3 mm 2 have been employed to irradiate the produced composites on a small localized region and wide areas respectively. The poly(dimethylsiloxane) foil, used to cover GO, confers flexibility to the created patterns and allows the oxygen degassing from GO. The quality and the fidelity of the patterns have been investigated by Atomic Force Microscopy (AFM). The ion beam induced structural changes in the coated and uncoated graphene oxide foils have been studied by Raman spectroscopy confirming that PDMS can be used as protecting layer to improve the quality of patterns obtained on graphene oxide by the 5.0 MeV C 3+ ions beam writing. Highlights: The polydimethylsiloxane as a coating of material improves the quality of the patterns realized by the ion lithography. Good  quality of reduced graphene oxide (rGO) due to its permeability to oxygen. Better homogeneity of the distribution of ions current during the patterning process. Lessening of the defects generation and the relaxation effects of the GO during the patterning by 5 MeV energy of heavy ions. Better performance of the capacitance prepared by ion-beam writing on GO covered with PDMS.